Birds of the Everglades Agricultural Area - Elise V. Pearlstine; Michelle L. Casler; Frank J. Mazzotti (EDIS, 2004)
A checklist of birds observed in the Everglades Agricultural Area. This checklist was developed through studies funded by the Everglades Protection District and the University of Florida, IFAS. November 2003.